2020
DOI: 10.1117/1.jbo.25.6.063811
|View full text |Cite
|
Sign up to set email alerts
|

High-power light-emitting diode array design and assembly for practical photodynamic therapy research

Abstract: Q. Spring, "High-power light-emitting diode array design and assembly for practical photodynamic therapy research," J. AbstractSignificance: Commercial lasers, lamps, and light-emitting diode (LED) light sources have stimulated the clinical translation of photodynamic therapy (PDT). Yet, the continued exploration of new photosensitizers (PSs) for PDT often requires separate activation wavelengths for each agent being investigated. Customized light sources for such research frequently come at significant financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…More importantly, the present study demonstrated that the type of multi-well plate used in these studies markedly affects the results obtained. It is common practice that black-walled multi-plates are used (19,33). The present study demonstrated that this may restrict light exposure to all the cells in all the wells.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…More importantly, the present study demonstrated that the type of multi-well plate used in these studies markedly affects the results obtained. It is common practice that black-walled multi-plates are used (19,33). The present study demonstrated that this may restrict light exposure to all the cells in all the wells.…”
Section: Discussionmentioning
confidence: 67%
“…LEDs can be arranged in into a planner array to increase the irradiated area even further. These arrays can be costly (>$1,000) (19), or low in price (<$25, the present study). Such advantages may render LEDs as a popular light modality in the 5-ALA-PDT of patients with CRC.…”
Section: Discussionmentioning
confidence: 93%
“…All in all, the use of LEDs for PDT was demonstrated in the mid-1990s by Schmid et al in brain tumours of canines treated with porifrin [ 52 ]. Presently, the rapid growth of LEDs led to the development of LED arrays of various wavelengths and handheld systems achieving the high power required for PDT [ 61 , 62 , 63 , 64 ]. For instance, array systems delivering a fluence rate of 100 mW/cm 2 demonstrated a 90% of cell death in ovarian cancer cell line using LED modules reaching a fluence of 50 J/cm 2 [ 62 ].…”
Section: Light Technology For Pdtmentioning
confidence: 99%
“…Presently, the rapid growth of LEDs led to the development of LED arrays of various wavelengths and handheld systems achieving the high power required for PDT [ 61 , 62 , 63 , 64 ]. For instance, array systems delivering a fluence rate of 100 mW/cm 2 demonstrated a 90% of cell death in ovarian cancer cell line using LED modules reaching a fluence of 50 J/cm 2 [ 62 ]. More recently, LEDs have been used for human breast cancer cell lines showing effective PDT without thermal issues [ 65 ] and for illumination of nanoparticles loaded with the photosensitizer in a human prostate tumour model [ 66 ].…”
Section: Light Technology For Pdtmentioning
confidence: 99%
“…17,18 A light-emitting diode (LED) has been successfully applied in the treatment of many skin diseases in PDT due to its high cover area and uniformity. [19][20][21][22] Other light modulators, such as a micromirror, are also used for PDT to achieve homogeneous irradiance by modulating the pulse duty factor. However, the coupling factor of such a device is limited by a digital mirror device.…”
Section: Introductionmentioning
confidence: 99%